2018
DOI: 10.12659/msm.913799
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion Fractures of the Ischial Tuberosity: Progress of Injury, Mechanism, Clinical Manifestations, Imaging Examination, Diagnosis and Differential Diagnosis and Treatment

Abstract: Avulsion fracture of the ischial tuberosity (AFIT) is a rare adolescent sports injury. At present, there is no consensus on its therapeutic paradigm, but conservative treatment appears to be the predominate choice. Furthermore, the degree of fracture displacement (DFD) remains as an important factor in determining whether AFIT needs internal fixation. The aim of the present study was to review and update the injury mechanism, clinical manifestations, imaging examination, diagnosis and differential diagnosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…There is no consensus on the treatment of these injuries. The decision for conservative versus surgical treatment is often based on the degree of fracture displacement, 17 but this is not always the case. A meta-analysis reviewing 596 patients concluded that surgical patients had a better rate of return to sports, advising consideration of surgery for "fragment displacement greater than 15 mm and high functional demands."…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the treatment of these injuries. The decision for conservative versus surgical treatment is often based on the degree of fracture displacement, 17 but this is not always the case. A meta-analysis reviewing 596 patients concluded that surgical patients had a better rate of return to sports, advising consideration of surgery for "fragment displacement greater than 15 mm and high functional demands."…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al [44] advocated for early ORIF regardless of displacement to avoid exacerbating injury symptoms and displacement, as has been reported in multiple case reports [4,20,44,45]. Conversely, Liu et al [8] reported that the decision to operate should be based on the patient's individualized requirements for functional recovery, such as early RTS, in addition to the degree of fracture displacement. However, less than a fourth of the athletes included specific information regarding fracture displacement, with a reported average of 2.5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature recommends surgical management of proximal hamstring if conservative therapy fails and the patient desires to return to higher level of competition/function, or there are complications including nerve involvement. 3,4,9 When operative repair is indicated, open reduction and internal fixation is generally the preferred method. 1e4,9…”
Section: Discussionmentioning
confidence: 99%